Podziały domatyczne grafów i ich produktów - Kijewska, Monika
Domatic partitions of graphs were investigated. The maximum number of classes of a domatic partition of a graph is called the "domatic number" of a graph. The all results in the work can be divided onto five parts. The first concerns the calculating of the domatic partitions of the path, the cycle, the complete bipartite graph and some domatically full graphs. These numbers were defined recursively.
Keywords: produkty grafów; grafy; podziały domatyczne grafów; liczby domatyczne grafów